An 8-32 GHz frequency synthesizer based on a wideband VCO array with bandwidth extension stage - Nehring, Johannes; Fischer, Georg; Weigel, Robert; Kissinger, Dietmar (8th German Microwave Conference, GeMiC 2014, 2019)
This paper proposes a wideband signal source covering a bandwidth of two octaves from 8 GHz to 32 GHz. The system is based on an array of three wideband voltage controlled oscillators (VCOs) for octave wide frequency synthesis and a post-synthesis stage which extends the bandwidth by another octave. The circuits were fabricated in a 0.35 µm SiGe bipolar technology with an ft/fmax = 170/250 GHz. The VCO tuning ranges are 28.9 %, 26.2 % and 24.7 % respectively. The average output power was measured to be −3.5 dBm. The single-sideband phase noise at 1 MHz offset has an average value of −100 dBc/Hz over the entire bandwidth of two octaves. The system blocks VCO array, bandwidth extension and output buffer consume a power of 175 mW, 277 mW and 150 mW.
CRIS-Team Scopus Importer:2021-04-20
Keywords: VCO; Voltage controlled oscillator; Wideband frequency synthesis